VD_FINDINFO HC / 2014 / 825 vom 7. Oktober 2014 - VD Tribunal cantonal (2014)
MESURE PROVISIONNELLE, DIVORCE, OBLIGATION D'ENTRETIEN, CONJOINT, REVENU HYPOTHÉTIQUE | 163 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)